Herpes viruses and human papilloma virus in nasal polyposis and controls - Ioannidis,Dimitrios (2015)
ABSTRACT INTRODUCTION: Chronic rhinosinusitis with nasal polyps is a multifactorial disease entity with an unclear pathogenesis. Contradictory data exist in the literature on the potential implication of viral elements in adult patients with chronic rhinosinusitis. OBJECTIVE: To compare the prevalence of human herpes viruses (1-6) and Human Papilloma Virus in adult patients with chronic rhinosinusitis with nasal polyps and healthy controls. METHODS: Viral DNA presence was evaluated by real-time polymerase chain reaction application to nasal polyps specimens from 91 chronic rhinosinusitis with nasal polyps patients and nasal turbinate mucosa from 38 healthy controls. RESULTS: Epstein-Barr virus positivity was higher in nasal polyps (24/91; 26.4%) versus controls (4/38; 10.5%), but the difference did not reach significance (p = 0.06). Human herpes virus-6 positivity was lower in nasal polyps (13/91; 14.29%) versus controls (10/38; 26.32%,p = 0.13). In chronic rhinosinusitis with nasal polyps group, 1 sample was herpes simplex virus-1-positive (1/91; 1.1%), and another was cytomegalovirus-positive (1/91; 1.1%), versus none in controls. No sample was positive for herpes simplex virus-2, varicella-zoster virus, high-risk-human papilloma viruses (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59) and low-risk-human papilloma viruses (6, 11). CONCLUSION: Differences in Epstein-Barr virus and human herpes virus-6 positivity among patients with chronic rhinosinusitis with nasal polyps and healthy controls are not statistically significant, weakening the likelihood of their implication in chronic rhinosinusitis with nasal polyps pathogenesis.